2021
DOI: 10.3389/fvets.2021.615310
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Flock Level Risk Factors of Sheep and Goat Abortion in Three Agroecology Zones in Ethiopia

Abstract: A cross-sectional survey was conducted to estimate the incidence of small ruminant abortion and identify its major causes and potential risk factors in goat and sheep flocks in three agroecology and production systems of Ethiopia. Information on pregnancy outcomes and management risk factors were collected for 299 goat and 242 sheep flocks. Blood samples were collected from 133 sheep and 90 goat flocks and tested for Coxiella burnetii, Brucella spp., Chlamydia abortus, and Toxoplasma gondii. A causal diagram o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 50 publications
3
25
2
Order By: Relevance
“…Abu-Dalbouh et al [6] reported that the overall prevalence (%) of T. gondii was 41.8% for aborted goats from Jordan. The variation in prevalence is due to variations in health management, feeding and watering systems, nutrition regimens for pregnant animals, biosecurity systems, geographical locations, season, weather, carrier intensification, parasitic genomic diversity, and genetic marker polymorphisms significantly influence the percentage of abortion [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Abu-Dalbouh et al [6] reported that the overall prevalence (%) of T. gondii was 41.8% for aborted goats from Jordan. The variation in prevalence is due to variations in health management, feeding and watering systems, nutrition regimens for pregnant animals, biosecurity systems, geographical locations, season, weather, carrier intensification, parasitic genomic diversity, and genetic marker polymorphisms significantly influence the percentage of abortion [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In sheep, abortions can be caused by viral [1,2] bacterial [3,4] or parasitic [5,6,7] factors, as well as diet deficiencies [8], poisoning [9] and extreme weather conditions [10]. Furthermore, in addition to the significant economic losses [11], any deaths caused by zoonotic pathogens can also pose a risk to breeders, animal keepers or veterinarians [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, inferences about the potential role and relative importance of abortigenic agents are often made from serological studies of livestock (Alemayehu et al, 2021;Okumu, John, Wabacha, Tsuma, & VanLeeuwen, 2019;Tolosa, Bezabih, & Regassa, 2010). This is due to a number of factors including a lack of national-level surveillance for syndromes such as abortions in livestock; restricted access to veterinary care for many subsistence farmers, who are therefore unable to investigate individual abortion events; and limitations in diagnostic laboratory capacity (e.g., little to no access to histopathology services or molecular diagnostic tests that could help to generate data on different aetiologies of abortion).…”
Section: Introductionmentioning
confidence: 99%